Filtrasi Air Sederhana Sebagai Solusi Peningkatan Kualitas Air Untuk Wilayah Sekitar Perkebunan Kelapa Sawit - Nurul Sari; Paujiah Paujiah; Nydia Amanda Putri; Rusliyani Rusliyani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Tegal Sari Village is one of the villages in Tanah Bumbu Regency, East Kalimantan. It is surrounded by oil palm plantations which results in the quality of the water being unfit for consumption. The people complain that the water is cloudy, has sediment, has a taste and also feels slippery. The absence of adequate water filtration is also an obstacle to the availability of clean water. This community service activity aims to increase the knowledge and quality of clean water in Tegal Sari Village, especially in RT 04 and RT 05. The method used in this research is to use the experimental method, which applies the principles of validation laboratory research, namely test the effect of one or more variables on other variables. The research was carried out in July and August 2022. The results showed that the knowledge of respondents before receiving material regarding simple water filtration was in the good category, namely as many as 9 people (37.5%), as many as 11 people (45.8%) had good knowledge. sufficient and as many as 4 people (16.6%) have less knowledge. Based on the results of the simple water filtration counseling pre-test, it is known that 37.5% of respondents have good knowledge, thus this intervention can help add insight and knowledge of residents regarding the physical quality of proper water consumption.